Looked at Life from Both Sides Now - Smith, Jillian E. (Life (Basel), 2014)
As the molecular top–down causality emerging through comparative genomics is combined with the bottom–up dynamic chemical networks of biochemistry, the molecular symbiotic relationships driving growth of the tree of life becomes strikingly apparent. These symbioses can be mutualistic or parasitic across many levels, but most foundational is the complex and intricate mutualism of nucleic acids and proteins known as the central dogma of biological information flow. This unification of digital and analog molecular information within a common chemical network enables processing of the vast amounts of information necessary for cellular life. Here we consider the molecular information pathways of these dynamic biopolymer networks from the perspective of their evolution and use that perspective to inform and constrain pathways for the construction of mutualistic polymers.